Numerical investigation of phase change material-based heat storage unit on cooling of mobile phone - Fok, Sai Cheong (2013)
This article presents the cooling of mobile phones using phase change material stored in a heat storage unit (HSU). In this study, the cooling performances of three HSU models at different power levels are examined using numerical simulation. Results show that for the same magnitude of heat source power, the melting start time and charging times can be extended if the heat sources and HSUs are distributed. Dimensional analysis shows that the melt fraction can be plotted against the product of Fourier and Stefan numbers to produce some generalized results for cases with low heat source power. At higher power, the Rayleigh number has to be included to take into account the effect of convection. The article also compares the heat source temperatures between plastic and aluminum enclosures.